Knowledge management to enhance competitiveness of VNPT Software Company = quản trị tri thức nhằm nâng cao năng lực cạnh tranh tại công ty phần mềm VNPT - Nguyễn, Việt Hưng (Khoa Quản trị kinh doanh, 2018)
CHAPTER 1. THEORETICAL BACKGROUND ON COMPETITIVENESS WITH KNOWLEDGE MANAGEMENT. CHAPTER 2. ASSESSING THE SITUATION OF COMPETITIVENESS WITH KNOWLEDGE MANAGEMENT IN VNPTSOFTWARE. CHAPTER 3. PROPOSAL ON SOLUTION TO ENHANCE COMPETITIVENESS ASSOCIATED WITH KNOWLEDGE MANAGEMENT IN VNPTSOFTWARE